2000
DOI: 10.1042/0264-6021:3530129
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase θ is translocated and phosphoinositide 3-kinase-dependently activated by noradrenaline but not angiotensin II in intact small arteries

Abstract: Diacylglycerol (DG) kinase (DGK) phosphorylates the lipid second messenger DG to phosphatidic acid. We reported previously that noradrenaline (NA), but not angiotensin II (AII), increases membrane-associated DGK activity in rat small arteries [Ohanian and Heagerty (1994) Biochem. J. 300, 51-56]. Here, we have identified this DGK activity as DGKθ, present in both smooth muscle and endothelial cells of these small vessels. Subcellular fractionation of artery homogenates revealed that DGKθ was present in nuclear,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
(82 reference statements)
4
12
0
Order By: Relevance
“…The initial transient increase in [ 33 P]PA in caveolae/rafts induced by NE was consistent with the transient activation of DGK-by this agonist (49). Recently, we showed that NE activates PI3-kinase/PKB signaling in RMSAs and that this pathway is essential for activation of DGK- (49). Here we show that caveolae/rafts are sites where PI3-kinase/PKB regulates DGK activity and provides evidence that DGK-is involved in the response.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The initial transient increase in [ 33 P]PA in caveolae/rafts induced by NE was consistent with the transient activation of DGK-by this agonist (49). Recently, we showed that NE activates PI3-kinase/PKB signaling in RMSAs and that this pathway is essential for activation of DGK- (49). Here we show that caveolae/rafts are sites where PI3-kinase/PKB regulates DGK activity and provides evidence that DGK-is involved in the response.…”
Section: Discussionsupporting
confidence: 82%
“…DGKs exist as multiple isoforms, and in RMSAs, NE activates DGK-in a PI3-kinase-dependent manner (49). In this study we confirmed the presence of DGK-in caveolae/rafts (Fig.…”
Section: Distribution Of [ 33 P]pipsupporting
confidence: 84%
See 1 more Smart Citation
“…DAG kinase-q q and -d d DAG kinase-q is another isozyme which has been found in the nucleus of several cell types, including rat arterial smooth muscle and endothelial cells, human MelJuso melanoma cells, COS-7 cells and IIC9 cells [12,13,40]. Quiescent IIC9 fibroblasts also express DAG kinase-d in the nucleus, but only the -q was activated in response to a-thrombin (see later) [13].…”
Section: Nuclear Dag Kinase Isoformsmentioning
confidence: 96%
“…Since the isotypes possess different domains in their primary structure, the mechanism of activation is also likely to differ among the isozymes. Membrane association (for example of DAG kinase-q) is necessary but not sufficient for the activation [40]. Most likely there must be other activation steps, such as phophorylation and/or interaction with small GTP-binding proteins [12].…”
Section: Regulation Of Nuclear Dag Kinase Activitymentioning
confidence: 98%